VD_FINDINFO AI 116/09 - 347/2011 vom 18. Juli 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, AFFECTION PSYCHIQUE, DÉBUT, MESURE D'ORDRE PROFESSIONNEL | 28 al. 2 LAI, 4 al. 1 LAI, 48 al. 2 LAI, 8 al. 1 LPGA